HIGIENISASI DAN APLIKASI URIN MANUSIA SEBAGAI PUPUK MINERAL PADA TANAMAN SAWI HIJAU (Brassica rapa) - Maria Prihandrijanti (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2011)
This research aims to produce mineral fertilizer from human urine that is safe for application to plants, and to compare the effectiveness of mineral fertilizers on crop using various soil types. The tested plant was mustard (Brassica rapa). The research work was started with elimination of pathogenic bacteria (Salmonella sp and Shigella sp) in the urine. This process was done by pH adjustment to 2 and 9. The urine was kept indoor and outdoor for one month prior to sterilization of the urine. Before the process begins hygienization, and measurements of the initial concentrations of total N, total P, K, potassium, TOC, fecal coli, and bacterial pathogens (Salmonella sp. and Shigella sp.) in fresh urine samples were measured. After one month re-analyses of the sample were conducted. The results showed that after one month there was no pathogens (Salmonella sp. and Shigella sp.) found. Urine was applied as fertilizer for the vegetable plant. The plant showed better growth than those without fertilizer application and those with NPK fertilizer application.